The Russian Jewish Question, Asked and Answered: Virtual Polemics Between Moisei Berlin and Yakov Brafman in the 1860s - Vassili Schedrin (Wrocławski Przegląd Teologiczny, 2018)
In the first half of the nineteenth century, Russian authorities had very limited knowledge of their Jewish subjects. The government relied more on its enlightened perceptions of the Jews and Judaism than on empirical observation. This situation changed radically in the 1860s, when at the onset of the Great Reforms era the government sought full and veritable information about all imperial subjects, including Jews, to facilitate the efficient policymaking by framing and answering Russian Jewish question. As a result, Russian language studies – written by Jews, Russian Christians, and Jewish converts to Christianity – on Judaism, Jewish history, society and culture started to appear. The article focuses on two such studies: Moisei Berlin’s “Essay on the ethnography of the Jewish population in Russia” (1861) and Yakov Brafman’s “Book of Kahal” (1869). Virtual polemics between Berlin and Brafman highlights fundamental differences between Russian studies of Judaism and Jewish life and classical Western European Christian Hebraism, namely, Russian scholars’ general lack of interest to the Talmud and to its alleged anti-Christian thrust, and almost exclusive focus on Jewish communal, social, and political institutes – kahal, chavurot (voluntary societies), beit din (rabbinical court) and others – and on their alleged anti-government nature.